Efficiency assessment of rubber plantation aid cooperation plants (RCOPs) in Songkhla province using data envelopment analysis (DEA) - Pradit-Ukrit, Sawarin; Sinthavalai, Runchana; Meemongkol, Napisphon (Asia-Pacific Journal of Science and Technology, 2017)
Nowadays, the quantity of Rubber Plantation Aid Cooperation Plants (RCOPs) in Songkhla Province has decreased continuously due to the lack of operational efficiency of each RCOP. The assessment of RCPOs efficiency should be considered. Thus, the objective of this study was to evaluate efficiency of 48 RCOPs in Songkhla by using Data Envelopment Analysis (DEA). Input factors, which were considered, were 1) operation cost, 2) number of member, 3) number of share and 4) rubber plantation areas; whereas output factors were volume of latex to purchase and revenue. Inputs and outputs were identified based on resource-based view theory (RBV). The result shows that 11 RCOPs are efficient, while 37 RCOPs are inefficient. In addition the result point out the target values for 37 RCOPs to improve their efficiency.